Evaluation of Medial Open Wedge High Tibial Osteotomy in Osteoarthritis of Knee - Kumar, Dr. Nitin; Chopra, Dr. R. K.; Jaiman, Dr. Ashish; Sodhi, Dr. Simarjot Singh; Mittal, Dr. Deepanshu; Bajaj, Dr. Prashant; Krishnan, Dr. Rohan (International Journal of Innovative Research in Medical Science, 2023)
Study Design: Prospective and Interventional Randomized Comparative Study. Duration of study: 18 months. Objective: 1. To estimate pain relief in a patient with primary degenerative osteoarthritis of knee after medial open wedge high tibial osteotomy (HTO) using visual analog scale(VAS). 2. To assess the change in femorotibial angle, weight bearing line deviation and tibial slope pre and post operatively. 3. To compare pre- and post-operative WOMAC (The Western Ontario and McMaster Universities Osteoarthritis Index) index. Methodology: This study is a prospective analysis of patients with the requisite inclusion criteria, done over 18 months in the Central Institute of Orthopaedics, VMMC & SJH, and New Delhi. It includes a total of 20 patients who were followed up for 6 months. After initial preoperative evaluation, they underwent medial open wedge HTO for primary degenerative osteoarthritis of knee. Post operatively, patients were assessed clinically, functionally and radiologically for the benefits & drawbacks of this technique. This study is used to compare the clinical, radiological and functional improvement using this technique in patients pre-operatively and post-operatively. Observation and Result: Based on our observation we conclude that the study suggest that medial open wedge HTO using TomoFixTM should be recommended for treatment of primary degenerative osteoarthritis of knee primarily involving the medial compartment of knee.